2016
DOI: 10.1080/14763141.2016.1186725
|View full text |Cite|
|
Sign up to set email alerts
|

Biomechanical differences between left- and right-handed baseball pitchers

Abstract: Left-handed baseball pitchers are thought to have a number of theoretical advantages compared to right-handed pitchers; however, there is limited scientific research detailing differences in the pitching mechanics of right- and left-handed pitchers. Therefore, this study sought to understand whether any kinematic and kinetic differences existed between right- and left-handed baseball pitchers. A total of 52 collegiate pitchers were included in this study; 26 left-handed pitchers were compared to 26 age-, heigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…The discrepancy may be due to the one-sided distribution of handedness and footedness. Biomechanical differences have been shown between left- and right-handed baseball pitchers and also for the elbow flexion, horizontal glenohumeral abduction and wrist coronal plane motion 57 . Furthermore, discrepancies in the test protocol existed in TT and ST compared to FtF, LI and RF.…”
Section: Discussionmentioning
confidence: 99%
“…The discrepancy may be due to the one-sided distribution of handedness and footedness. Biomechanical differences have been shown between left- and right-handed baseball pitchers and also for the elbow flexion, horizontal glenohumeral abduction and wrist coronal plane motion 57 . Furthermore, discrepancies in the test protocol existed in TT and ST compared to FtF, LI and RF.…”
Section: Discussionmentioning
confidence: 99%
“…This paper included fourteen right-handed and three left-handed pitchers. Further research should examine the differences of weighted-ball training between right- and left-handed pitchers, as previous research has suggested differences in range of motion, humeral retroversion, and biomechanics depending on the dominant throwing arm ( Solomito, Ferreira & Nissen, 2017 ; Werner et al, 2010 ; Takenaga et al, 2017 ). It is therefore possible that pitchers should have different throwing, mobility, and strength programs depending on which arm is dominant.…”
Section: Discussionmentioning
confidence: 99%
“…The clinician scientist also performs sub group analyses for left and right handers, as these sub populations have demonstrated different clinical phenotypes, including demonstrating different height, 55 mass, 50 humeral torsion, 56,57 and pitch velocity. 58 The clinician scientist observed that there is still a difference in total shoulder rotation between injured and non-injured pitchers, which after controlling for all confounders, is 12º. Further when analyzing left and right handers separately, left handers demonstrated a 9º difference and right handers demonstrated a 15º difference.…”
Section: Application In Sport Using Baseball As the Examplementioning
confidence: 99%